2023
DOI: 10.21037/qims-22-701
|View full text |Cite
|
Sign up to set email alerts
|

The new fast kilovoltage-switching dual-energy computed tomography for measuring bone mineral density

Abstract: Background: The update in technology may impact the accuracy in measuring bone mineral density (BMD). However, the application of the new fast kilovoltage (kV)-switching dual-energy computed tomography (DECT) for BMD measurement has not yet been reported. This study aimed to examine the accuracy and precision of the new fast kV-switching DECT in measuring BMD and to evaluate its applicability in clinical BMD measurement.Methods: Forty sets of the new fast kV-switching DECT scans and one quantitative computed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Excellent correlation was found between the QCT-BMD and HAP-BMD values of the internal inserts in this study, which further verified previous investigations on the reliability of QCT in the measurement of BMD ( 27 , 28 ). A prior study also verified the accuracy of QCT in measuring BMD based on the European spine phantom (ESP) ( 29 , 30 ). Of note, both our and previous studies on phantom found that the BMD value measured by QCT was usually higher than the HAP concentrations value ( 28 ).…”
Section: Discussionmentioning
confidence: 86%
“…Excellent correlation was found between the QCT-BMD and HAP-BMD values of the internal inserts in this study, which further verified previous investigations on the reliability of QCT in the measurement of BMD ( 27 , 28 ). A prior study also verified the accuracy of QCT in measuring BMD based on the European spine phantom (ESP) ( 29 , 30 ). Of note, both our and previous studies on phantom found that the BMD value measured by QCT was usually higher than the HAP concentrations value ( 28 ).…”
Section: Discussionmentioning
confidence: 86%
“…Zhou et al ( 32 ) demonstrated in vivo that fast-switching DECT can accurately evaluate phantomless BMD, and Ca-fat and HAP-fat have similar and optimal predictive abilities, which is consistent with our findings. Wang et al ( 36 ) also reported a highly positive correlation between BMD assessment derived from new fast-switching DECT and QCT (R 2 =0.912) and found that the relative error of the new fast-switching DECT was smaller than that of QCT. In addition, the consensus for applying QCT recommends collecting two whole vertebral bodies in the T12–L3 range, typically the L1–L2 vertebral bodies ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 92%
“…Through continuous energy spectrum acquisition by dual-energy computed tomography (DECT), this principle can be utilized to evaluate material-specific attenuation behavior, which is characterized by disparate attenuation at different energy levels, and to obtain material-specific images ( 10 , 11 ). Consequently, the DECT enables differentiation, classification, and quantification of the mass density of various materials ( 12 - 14 ). Accordingly, iodine-specific images can represent iodine content in the tissues and provide quantitative enhancement information, which is beneficial for making the transition from qualitative to quantitative evaluation of contrast-enhanced CT images ( 12 ).…”
Section: Introductionmentioning
confidence: 99%